Photovoltaic waste as source of valuable materials: A new recovery mechanical approach. (20th January 2023) - Fiandra, Valeria; Sannino, Lucio; Andreozzi, Concetta
Abstract: End-of-life photovoltaic modules are hazardous waste belonging to the category of waste from electrical and electronic equipment. They contain environmentally hazardous substances, poorly biodegradable materials but also valuable materials. The recovery of these last is the main goal of PV-waste treatments. In order to facilitate the recovery and produce released fractions that are suitable for the recycling of glass, Silicon, Silver, Copper, Lead and Aluminium, the mechanical technics applied in the management of all e-waste without differentiation by type, are the most commonly used. However, a new and appropriate management strategy is required to maximize the recovery efficiency and improve the quality of recovered materials. This paper aims to identify and overcome the critical points in the PV-waste management mechanical processes and provides information on more efficient routes for their treatment. It aims to shed some light on the usefulness of adopting a specific and dedicated approach, to optimize the recovery rate and recovered materials purity level to send to recycling. A new mechanical process of separation and recovery of materials is proposed and compared with a typical conventional e-waste treatment process. The developed process makes improvements in the materials separation step, initial stage conditioning the process, making it more efficient than the conventional one. Highlights: A new mechanical process for the materials recovery from PV-waste is developed. Criticality of the treatments used for WEEE is highlighted in the case of PV-waste. Emphasis is given to the use of specific treatments in the PV-waste management. The usefulness of a delamination pre-treatment for PV-waste is highlighted.